Pengaruh Pelatihan Berprilaku Caring Terhadap Kemampuan Caring Mahasiswa Praktek Profesi Fakultas Keperawatan Unand di RSUP Dr.M.Djamil Padang : The Effect of Caring Behavior Training on Ability Caring Skills of Professional Practice Students of the Faculty of Nursing Unand at Dr.M.Djamil Hospital Padang - Reni Prima Gusty (NERS Jurnal Keperawatan, 2013)
Caring nurse behavior will be guarantee quality care, because Caring is the essence of nursing between nurses means responsive to the clients . Therefore Unand nursing faculty seeks caring training to make students better prepared to provide quality nursing care when the practice of the profession and to produce graduates who are ready kerja.Penelitian examines the effect of training on kemampun caring Caring Professions School of Nursing Students Practice Unand . This type of research experimentation Quasi one-group pretest- posttest design. Students study subjects practice the profession in Dr M Djamil Padang Hospital numbered 22 peoples and spread across nine rooms are neurologi , pulmonary , male internal , female internal , high care unit, female surgical , male surgical , trauma centere and recovery room . Instruments is queationer that measure eight capability caring consist of hear clients with caring attentive, giving a sense of security, a touch, build trusting relationships, responsibility, information, sensitive to the client, and respecting the client . Students were trained for 2 days with bedside teaching methods. Analysis of the data processed using Marginal homogenity test to see the effect of training on kemampun caring Caring Professions School of Nursing Students Practice Unand . The results showed that there is an increased ability to behave in the caring professions students of the Faculty of Nursing Unand practice after the training given to the value of p = 0.000 . Using suggestions caring approach to training in small groups more able to improve psychomotor skills of students in the practice of land . And can be used by professionals as part of main graduation loaded